Albanian songs of frontier warriors and their antiquity - Berisha, Labinot (Technium Social Sciences Journal, 2022)
Albanian heroic songs with a range of values and peculiarities, with the thematic and poetic world, as rich as independent and ancient, and with different layers, could not be created immediately and only in one period. It took time and skill for singers and oral conductors to create, spread and carry from one individual to another, from one generation to the next. Albanian heroic songs are not only important for the many linguistic expressive values that the rich thematic and motivational world has, but they also enable the best knowledge of the oral epic of the peoples of Southeast Europe and especially of the epic of the peoples of the Balkans. What justifies the antiquity, but at the same time the great importance of our heroic songs, is the fact that they express the world of the singers who sing them, their worldview and the world they belong to. They express the honor, manliness, faith, virtues, customs and habits that our man has used over the centuries. Dealing with the comparison of Albanian songs of frontier warriors with ancient epics, I have noticed a series of similarities with some ancient epics, especially with the "Iliad" and "Odyssey", which directly testify to their antiquity.